Pengalaman Keluarga Dalam Mencari Pengobatan Pada Gangguan Jiwa - Noorwahyu Trihidayati; Iman Permana (Jurnal Keperawatan Muhammadiyah, 2020)
Background: Seek treatment is a continuous process, where the symptoms of the disease suffered have increased and can gradually be seen, evaluated and finally treated through the initiation of specific interventions Early symptoms of mental disorders are not always seen by lay people, so the search for treatment for psychosis is sometimes sometimes delayed. Delays in seeking treatment will lead to worse results. The process of seeking treatment will be repeated until recovery goals are achieved. Objective: To find out family experiences in seeking treatment in patients with mental disorders. Methods: The method used in this review literature by analyzing several articles using data base at EBSCO, Science direct, Pupmed and Google scholar, then extraction using the keywords "Help seeking behavior" OR "treatment seeking behavior" AND mental illness "OR Mental disorder" OR "Health mental" OR first episode psychosis "AND" Qualitative "In the 2015-2019 period to find articles that fit the inclusion and exclusion criteria then a review was conducted. Result : The first search results collected 152 articles from Pumped, 287 Science direct 1410 articles, Google scholar articles, and 191 articles from EBSCO, the second attempt by entering "Duplication" of a total of 1410 articles. The third attempt with m Including "linked full text" available, abstract, and limited references from 2015 -2019 inclusive and exclusive criteria obtained as many as 172 articles, the last 17 articles that will be analyzed later. From the results. Analysis obtained several themes, namely: Search for health treatment mental and barriers in seeking treatment. Conclusions :some studies discuss seeking treatment in mental disorders: supernatural consultation with physicians, scholars or spiritual treatments that are culturally appropriate for handling mental health problems and for health services such as psychiatrists or doctors / nurses who professional.Inhibition of seeking treatment occurs because of the stigma associated with mental patients, lack of knowledge is also due to socioeconomic.